PELATIHAN KEPADA GURU GURU MAS PROYEK UNIVA MEDAN DALAM MEMAHAMI KETERAMPILAN DASAR MENGAJAR GURU DALAM MEMBELAJARKAN SISWA - Nurhasnah Manurung; Samio Samio (Jurnal Pengabdian Mitra Masyarakat, 2021)
Associated with the implementation of the 2013 Curriculum Based on Higher Order Thinking Skills (HOTS), basic teaching skills must be possessed by every teacher in teaching students. The teacher is the holder of an important role in student learning activities because in the process of these activities there are a number of actions of teachers and students as a reciprocal relationship. Teachers who have competence, will be better able to create an effective learning environment. A teacher is required to have a number of basic teaching skills in order to manage his class, so that student learning outcomes can achieve satisfactory results. The appearance of each teacher in both exact and non-exact fields, obtained an overview of the teacher's ability in practice to implement basic teaching skills according to the field of study that each teacher is teaching. It seems that all teachers are enthusiastic in implementing the eight basic teaching skills. Notes from the observers for each teacher who appear, are made as a feddback to analyze the strengths and weaknesses during peer teaching, which were previously conveyed by the coaching team if there were corrections to the weaknesses and strengths of each teacher who appeared for mutual improvement.